PENGARUH BIAYA LINGKUNGAN DAN KEPEMILIKAN ASING TERHADAP KINERJA KEUANGAN - Upinius; Yusnita, Heni (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This research is to examine the influence of Environmental Costs and Foreign Ownership on Financial Performance. Environmental costs are measured by the percentage of environmental costs compared to company profits. Foreign share ownership is measured by the percentage of shares owned by foreign parties compared to the number of company shares. Meanwhile, financial performance is measured by Return On Assets (ROA). The sample from this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) from 2019 to 2022, namely 13 companies. The sampling method is purposive sampling. The data analysis method used in this research is multiple regression analysis. The results of this research indicate that environmental costs has a negative effect on financial performance, and foreign share ownership has a positive effect on financial performance.